2021
DOI: 10.1002/jbm4.10454
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Bone Collagen Cross‐Linking in Osteogenesis Imperfecta/Bruck Syndrome Caused by Compound Heterozygous PLOD2 Mutations

Abstract: Bruck syndrome (BS) is a congenital disorder characterized by joint flexion contractures, skeletal dysplasia, and increased bone fragility, which overlaps clinically with osteogenesis imperfecta (OI). On a genetic level, BS is caused by biallelic mutations in either FKBP10 or PLOD2 . PLOD2 encodes the lysyl hydroxylase 2 (LH2) enzyme, which is responsible for the hydroxylation of cross‐linking lysine residues in fibrillar collagen telopeptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…The detrimental consequences of lack of LOX activity on collagen fibrillogenesis are seen after incubation of osteoblasts with the enzymatic inhibitor, β-aminopropionitrile (BAPN), as a result of which crosslinks and osteoblast differentiation are dysregulated (Turecek et al 2008 ). This is also in agreement with the defective crosslinking seen in patients with OI/Bruck syndrome patients with PLOD2 and FKBP10 mutations (Gistelinck et al 2020 ). This also highlights the need for impeccable coordination with COPI trafficking which delivers the FKBP65 back to the ER to make it available for procollagen hydroxylation.…”
Section: Extracellular Processingsupporting
confidence: 88%
“…The detrimental consequences of lack of LOX activity on collagen fibrillogenesis are seen after incubation of osteoblasts with the enzymatic inhibitor, β-aminopropionitrile (BAPN), as a result of which crosslinks and osteoblast differentiation are dysregulated (Turecek et al 2008 ). This is also in agreement with the defective crosslinking seen in patients with OI/Bruck syndrome patients with PLOD2 and FKBP10 mutations (Gistelinck et al 2020 ). This also highlights the need for impeccable coordination with COPI trafficking which delivers the FKBP65 back to the ER to make it available for procollagen hydroxylation.…”
Section: Extracellular Processingsupporting
confidence: 88%
“…Depending on the state of Lys hydroxylation in collagen telopeptides, 2 major cross-linking pathways are evolved: Lys ald - and Hyl ald -derived cross-links [63] , with the latter displaying enhanced stability over the former. Since LH2 is responsible for Lys hydroxylation in telopeptides, its activity is key to determining the stability, that is, “quality”, of collagen cross-linking [ 8 , 20 , 61 ]. While LH2 hyperactivity has been implicated in fibrosis for decades [ 59 , 60 ], mounting evidence suggests that LH2 upregulation can also drive proinvasive and prometastatic tumor behaviors across many different cancers.…”
Section: Resultsmentioning
confidence: 99%
“…However, the stability of collagen fibrils also depends on the quality/type of cross-links formed, not necessarily the quantity of cross-links alone. Collagens containing LH2-mediated stable cross-links are more resistant to degradation than those not modified by LH2 [ 8 , 20 , 61 ]. Moreover, such a stiffened and highly cross-linked tumor ECM may diminish accessibility of immune cells to the cancer cells within the TME.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a LH2 mutant zebra sh model, Gistelinck et al reported that Lys in the α1 C-telo of bone type I collagen (16 C ) was not hydroxylated in the mutant 24 , though neither Lys hydroxylation of the α1 and α2 N-telo domains nor the Hyl ald -or Lys ald -derived cross-links was analyzed in this study. More recently, Gistelinck et al reported detailed type I collagen phenotypes in bone obtained from a patient with Bruck syndrome 25 .…”
Section: Introductionmentioning
confidence: 99%